Financial Literacy, Educational Background, and Materialistic Among Gen Z in Indonesia - Dewi, Sinta; Muchtar, Asiah (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2023)
This study aims to determine the influence of financial literacy, gender, and educational background on the materialism of Generation Z Indonesians in 2022. Data were gathered by surveying 592 respondents and analysed with the Ordinary Least Squares (OLS) method, resulting in three main findings. First, the influence of financial literacy is proven to reduce materialism significantly. Second, there is no difference between males and females in the materialism they believe in. Third, there is an influence of educational background on materialism. This study also finds that students with an economic and business education background are more materialistic than non-economic and business students. Furthermore, the findings of this study indicate that knowledge of financial concepts, products, and services is not enough to reduce materialism. Therefore, interventions are needed to encourage the financial attitude or individual perception of long-term finances, which is essential for achieving financial resilience and financial well-being, especially for Generation Z Indonesians.